2019
DOI: 10.1001/jamacardio.2019.3788
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Income Changes and Incident Cardiovascular Disease

Abstract: IMPORTANCE Higher income is associated with lower incident cardiovascular disease (CVD). However, there is limited research on the association between changes in income and incident CVD. OBJECTIVE To examine the association between change in household income and subsequent risk of CVD. DESIGN, SETTING, AND PARTICIPANTS The Atherosclerosis Risk In Communities (ARIC) study is an ongoing, prospective cohort of 15 792 community-dwelling men and women, of mostly black or white race, from 4 centers in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 38 publications
(71 reference statements)
2
25
0
1
Order By: Relevance
“…Consistent with previous research, our findings reveal that Gender, Age, BMI, and smoking were important predictors of CVD risk 12 , 21 . Earlier studies have established an association between parental income 72 , sedentary duration 73 , skipping breakfast 74 , self-image 75 , and depressive symptoms 76 and a higher likelihood of CVD risk, and our study results further substantiated this as these factors are found to be critical predictors of CVD risk. In addition, some predictors emerged as important for specific algorithms but not for others.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous research, our findings reveal that Gender, Age, BMI, and smoking were important predictors of CVD risk 12 , 21 . Earlier studies have established an association between parental income 72 , sedentary duration 73 , skipping breakfast 74 , self-image 75 , and depressive symptoms 76 and a higher likelihood of CVD risk, and our study results further substantiated this as these factors are found to be critical predictors of CVD risk. In addition, some predictors emerged as important for specific algorithms but not for others.…”
Section: Discussionsupporting
confidence: 87%
“… 13 The causal relationship between lower socioeconomic status and poorer prognosis has also been confirmed from a longitudinal study exploring income changes with incident cardiovascular events including HF. 14 A recent global between-country analysis showed that income inequality, rather than income level alone, may impact on HF outcomes to a similar degree as do major comorbidities. 15 The relationship between lower socioeconomic status and worse clinical outcome could be bidirectional due to higher economic burden imposed by HF per se or HF-related comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis (AS) is a chronic multifactorial disease with high incidence and mortality rates worldwide [ 1 ]. Currently, it is well-known that the pathophysiological mechanisms and aetiology of AS include the dysregulation of lipid metabolism, activation of inflammatory factors and functional activation of various cells in the blood vessels, such as lymphocytes and macrophages.…”
Section: Introductionmentioning
confidence: 99%